Dogs packing goods to the mines, east side of the Klondike River Bridge, Dawson, Yukon Territory, ca. 1898. - University of Washington Libraries. Special Collections Division
Caption on image: "Dogs packing goods to the mines" PH Coll 246.84 [Meed journal: "Dogs packing goods to the mines on east side of the Klondike River Bridge. Summer time in the Klondike."]. Klondike Gold Rush. To order a reproduction, inquire about permissions, or for information about prices see: http://www.lib.washington.edu/specialcollections/services/reproduction/reproduction Please cite the Order Number